DECONSTRUCTION OF THE SYMBOLIC MEANING OF THE KERATON SURAKARTA ARCHITECTURE - S. Pitana, Titis; Semadi Astra, I Gde; Suastika, I Made; Yudha Triguna, I. B. Gde (E-Journal of Cultural Studies; Vol. 4, No. 2 Juli 2010, 2012)
This dissertation is the result of a study entitled ”Deconstruction ofthe Symbolic Meaning of the Keraton Surakarta Architecture.” This studyis intended not to understand the Keraton Surakarta architecture as aphysical materialization of architectural planning and design. Rather, inthis study, the Keraton Surakarta is the material object of a study on thedeconstruction of the symbolic meaning which focuses on three mainproblems: (1) the cause of the deconstruction of the symbolic meaningtoward the Keraton Surakarta architecture; (2) the deconstruction processof the symbolic meaning; and (3) the implication of the deconstructiontoward the social-cultural life of the keraton people and Surakarta society.
Keywords: deconstruction, symbol, architecture, Keraton Surakarta